Perancangan Promosi Digital Produk Home Industry Berbasis OpenChart di Kabupaten Bengkalis - Firdaus, Raihan; Annas, Firdaus; Wira Yudha, Gerli (Yayasan Lembaga Studi Makwa, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Bengkalis Regency face major challenges in marketing home industry products such as cakes, chips, handicrafts and food, mainly due to high competition in the market and limitations in production capacity. These issues affect the competitiveness and sustainability of MSME businesses. This research aims to design web-based digital promotional media using the OpenCart application to support MSME product marketing efforts effectively and efficiently. The research method used is the Research and Development (R&D) model with the ADDIE approach which includes the Analysis, Design, Development, Implementation and Evaluation stages. The results of this research are in the form of a web-based promotion system using the OpenCart platform, which is designed to make it easier for MSMEs to market their products more widely through digital media. The research findings show that OpenCart-based promotional media is able to improve the competitiveness of MSMEs by providing excellent features such as product catalogs, stock management, integration of payment methods, and ease of order management. This system also helps overcome production problems by increasing the efficiency of order management so that MSMEs can better manage spikes in demand. With this web-based promotion system, MSMEs can overcome several major problems, such as the difficulty of competing in a competitive market and limited production capacity. This research provides relevant and applicable solutions for MSME players, especially in facing the digitalization era. This promotional media is expected to be a model that can be replicated in various other regions.